2015
DOI: 10.1177/1076029615595878
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Factor Xa-Specific Chromogenic Substrate Assays and the Determination of Pharmacokinetics of Fondaparinux

Abstract: Fondaparinux (FPX), a synthesized factor Xa inhibitor, is one of the most popular anticoagulants for the prevention of postoperative venous thromboembolism (VTE). Although routine monitoring is not required, the bleeding adverse events cannot be neglected, and the measurement of anti-Xa activity is expected to be monitored. The primary purpose of this study is to evaluate the performances of 2 chromogenic assays for the detection of anti-Xa activity. Furthermore, the pharmacokinetics of FPX was examined using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…The anti-Xa activity of 2.5mg inversely correlates with BW between 40 and 100kg. 197 In patients with VTE weighing <50kg, the 2.5mg fixed dose should be used cautiously 195 and is contraindicated by the FDA. 198 On the other hand, a small study on morbidly-obese patients showed an anti-Xa activity below target in ≈50% of patients.…”
Section: Fondaparinuxmentioning
confidence: 99%
“…The anti-Xa activity of 2.5mg inversely correlates with BW between 40 and 100kg. 197 In patients with VTE weighing <50kg, the 2.5mg fixed dose should be used cautiously 195 and is contraindicated by the FDA. 198 On the other hand, a small study on morbidly-obese patients showed an anti-Xa activity below target in ≈50% of patients.…”
Section: Fondaparinuxmentioning
confidence: 99%
“…On the other hand, it has been reported that elevated anti-Xa activity by FPX was observed in patients with renal impairment but not in patients with body weight <50 kg or age >75 years. 27) However, no significant correlation between anti-Xa activity and the occurrence of postoperative bleeding was observed following thromboprophylaxis with FPX. 28) Therefore, together with the results of this study, bleeding following thromboprophylaxis after TKA or THA might not be related to the renal clearance of FPX.…”
Section: Discussionmentioning
confidence: 99%
“…27) However, no significant correlation between anti-Xa activity and the occurrence of postoperative bleeding was observed following thromboprophylaxis with FPX. 28) Therefore, together with the results of this study, bleeding following thromboprophylaxis after TKA or THA might not be related to the renal clearance of FPX. To determine whether an association exists between anti-Xa activity and bleeding events in patients with thromboprophylaxis with FPX, further investigations are necessary.…”
Section: Discussionmentioning
confidence: 99%
“…The in vitro anti-FXa activity was determined using a commercial BIOPHEN™ kit (HYPHEN BioMed, France) based on a previously described two-stage chromogenic substrate method. 31 In short, the synthetic unmodified heparin heptasaccharide 20 and Arixtra were dissolved in 50 mM Tris buffer solution ( pH 7.4) containing 150 mM NaCl and 1% (w/v) BSA in different concentrations, respectively. Factor Xa (FXa), antithrombin (AT) and the chromogenic substrate S-2765 were carefully prepared according to the manufacturer's instruction before the assay.…”
Section: Determination Of the Anticoagulant Activity In Vitromentioning
confidence: 99%